AN ANALYSIS OF SLANG WORDS IN â€œDEADPOOL 2â€ MOVIE DIRECTED BY DAVID LEITCH - Nur, Dewi Lestari; Rosida, Ana (JOURNAL OF ADVANCED ENGLISH STUDIES, 2020)
Slang words is generally considered as informal style of speech which is used by groups of people in particular community. It can be in the form of a single word, phrase, or sentence. This study is conducted to investigate the slang words found in Deadpool 2 movie. The main objectives of this study are analyzing the lexical and contextuan meaning, types of slang, and the root of slang words. In order to answer the formulated problem, the method used for this study is descriptive qualitative method. The primary source of this study is Deadpool 2 movie directed by David Leitch published in 2018. Meanwhile, the secondary sources of this study are books, e-journal, and e-articles that contained related theories. The theories that used in this research are Mansoer Patedaâ€™s Lexical and Contextual Meaning Theory and Allan and Burridge Types of Slang Theory. According to the result of the research, there are 74 words and phrases found in Deadpool 2 movie. There are five types of slang words also found in the movie. Those are fresh and creative, flippant, clipping, imitative and acronym. It is also found that each slang words has their own root which is categorized into swear words, religion-related, impolite call, sweet call, and expressions.